IGF1R as druggable target mediating PI3K-delta inhibitor resistance in a murine model of chronic lymphocytic leukemia - Scheffold, Annika; Dietrich, Sascha (Blood, 2019)
Targeted therapy is revolutionizing the treatment of cancers, but resistance evolves against these therapies and derogates their success. The phosphatidylinositol 3-kinase delta (PI3K-delta) inhibitor idelalisib has been approved for treatment of chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma, but the mechanisms conferring resistance in a subset of patients are unknown. Here, we modeled resistance to PI3K-delta inhibitor in vivo using a serial tumor transfer and treatment scheme in mice. Whole-exome sequencing did not identify any recurrent mutation explaining resistance to PI3K-delta inhibitor. In the murine model, resistance to PI3K-delta inhibitor occurred as a result of a signaling switch mediated by consistent and functionally relevant activation of insulin-like growth factor 1 receptor (IGF1R), resulting in enhanced MAPK signaling in the resistant tumors. Overexpression of IGF1R in vitro demonstrated its prominent role in PI3K-delta inhibitor resistance. IGF1R upregulation in PI3K-delta inhibitor-resistant tumors was mediated by functional activation and enhanced nuclear localization of forkhead box protein O1 transcription factors and glycogen synthase kinase 3 beta. In human CLL, high IGF1R expression was associated with trisomy 12. CLL cells from an idelalisib-treated patient showed decreased sensitivity to idelalisib in vitro concomitant with enhanced MAPK signaling and strong upregulation of IGF1R upon idelalisib exposure. Thus, our results highlight that alternative signaling cascades play a predominant role in the resistance and survival of cancer cells under PI3K-delta inhibition. We also demonstrate that these pathway alterations can serve as therapeutic targets, because inhibition of IGF1R offered efficacious salvage treatment of PI3K-delta inhibitor-resistant tumors in vitro and in vivo.
Gesehen am 14.10.2019